2017
DOI: 10.17269/cjph.108.6079
|View full text |Cite
|
Sign up to set email alerts
|

The association of exposure to suicide-related Internet content and emergency department visits in children: A population-based time series analysis

Abstract: OBJECTIVES: Suicide-related emergency department (ED) visits by children are increasing in tandem with suicide-related Internet content. Following the announcement of Amanda Todd's suicide, her YouTube video received widespread views, providing an opportunity to explore this association.METHODS: Our research question was: Among Ontario children age 11-17 years, was the release of Amanda Todd's YouTube video following her death announcement in October 2012 associated with an increase in average monthly ED visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, the time-related analysis of images did not indicate any effects of imitation or reinforcement [31]. A separate time series analysis did not find an increase in average monthly emergency department visits for suicide-related diagnoses in Ontario children aged 11-17 years following posting and publicity of a young person's YouTube video who took their own life [37]. This showed the young person holding up cards telling a story of bullying, mental health issues, and self-harm, with an image of self-harm injuries at the end.…”
Section: Imitationmentioning
confidence: 80%
See 4 more Smart Citations
“…However, the time-related analysis of images did not indicate any effects of imitation or reinforcement [31]. A separate time series analysis did not find an increase in average monthly emergency department visits for suicide-related diagnoses in Ontario children aged 11-17 years following posting and publicity of a young person's YouTube video who took their own life [37]. This showed the young person holding up cards telling a story of bullying, mental health issues, and self-harm, with an image of self-harm injuries at the end.…”
Section: Imitationmentioning
confidence: 80%
“…There was also a significant association between wound grade and number of comments [31]. Time-related analyses did not support any effects of contagion or reinforcement [31,37] • Participants reported that a lack of moderation on Tumblr and the freedom to view and share the most stark and severe images had led to normalization and exacerbation of self-harm. One participant stated that their self-harm had escalated from little gashes to severe injuries and cutting through arteries [9] Reduction in self-harm urges…”
Section: Triggeringmentioning
confidence: 99%
See 3 more Smart Citations